The Development Of Chemistry Virtual Laboratory On Colloidal System To Improve Generic Science Skills - Khaeruman, Khaeruman; Darmatasyah, Darmatasyah; Hulyadi, Hulyadi (IKIP Mataram, 2017)
This study animed to obtain the from and feasibility of teaching materialsinteractive multimedia based on virtual laboratory on colloidal systemconcept for SMA. The development model used in this study was 4D namelyDefine, Design,, Development, And Disseminate. But in this study only cameto Development stage. The velopment result was validated by 2 lecturers, 1teacher and 10 students in Ma Nurul Muhsinin. Based on the assessment oftwo lecturers as validatorn got the average (71,3%) with the appropriatecategory, the validation result from the subject teachers got percentage of(77,7%) with appropriate category, and the limited trial result by 10 studentsgot percentage of (80,8%) with decent category. So it can be concluded thatthe feasibility of interactive multimedia based on virtual laboratory oncolloidal system material for SMA/MA/SMK was feasible to use.